Praxis et organisation - Olivier Voirol (Communication)
Today critical theory and practices appear to wane. This decline is related to the crisis which is currently beleaguering the “praxis paradigm,” the main referent to critical thought. Sensitive to the practical organization of communication between subjects and their “world,” this paradigm challenges all formal organization that dehumanizes, desocializes and distorts knowledge. After reviewing some of the factors that brought about the collapse of the paradigm, the author opens up a theoretical venue to a possible reconstruction.